English Teachers' Experiences in Developing Students' Speaking Skills with a PBL Model at Junior High School in Indonesia - Aisyifa, Wildanita Risna Anggi; Hikmat, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2024)
Purpose: To find out what problems exist in the classroom when students are learning and what solutions are commonly used to solve these problems, then by using what strategies are used by english teachers in implementing the Problem-Based Learning model to develop the speaking skills of intermediate level students. Methodology: This research uses a method involving an approach that emphasizes on teachers' experiences called phenomenology through semi-structured interviews, and classroom observations used to analyze how teachers implement problem-based learning in developing secondary school students' speaking skills and data collected using a qualitative research approach. Results: The various data collection methods provide a comprehensive understanding of the effectiveness of classroom learning and the learning environment. The data show that the problem-based learning model focusing on developing the speaking skill of junior high school students is still quite ineffective in increasing students' confidence and fluency in English conversation because most students still have difficulty in pronunciation, teachers need to have more additional strategies in creating an environment that influences students' learning development, especially in developing their speaking skill. Applications/Originality/Value: To help students understand complex academic subjects in English, this study found that teachers need a strategy that keeps students from getting bored in class and that serves to increase students' focus on English speaking skills using problem-based learning model. A differentiated curriculum can also better balance academic and conversational language development by focusing on these areas, ensuring that students achieve both. The results of this study add to our understanding of immersive language teaching and provide guidance for improving comparable initiatives to enhance student performance.